Adipokines and C-reactive protein as indicators of MetS presence in obese Greek children: The Healthy Growth Study. (2021) - Vassilopoulou, Emilia; Giannopoulou, Emmanouela; Theodosiou, Argiris; Karaglani, Eva; Manios, Yannis; Moschonis, George
Graphical abstract: Highlights: MetS occurs in a 1 out of 4 obese children and increases the future risk of serious health complications. The serum level of adiponectin decreases while leptin increases as body weight increases, in the understudy children group. The serum level of the inflammatory marker CRP increases significantly as body weight increases in the understudy population. Adipokines and CRP can distinguish the children with Metabolic Syndrome as compared to children with no Metabolic Syndrome. Abstract: Background: Metabolic syndrome (MetS) occurs in a proportion of overweight and obese children and increases their future risk of serious health complications, even in adolescence and young adulthood. We aimed to explore the role of certain adipokines and inflammatory markers in identifying children with MetS. Methods: This study is a secondary analysis of data coming from the Healthy Growth Study, a cross-sectional study conducted with schoolchildren in Greece. The present study included data from a representative sample of 1376 schoolchildren (mean age: 11.19 ± 0.66 years), recruited from 77 primary schools in four large regions in Greece. Anthropometric, clinical and biochemical data were recorded. Children's body weight status and the presence of MetS were determined and their correlation with the serum levels of leptin, adiponectin and C-reactive protein (CRP) was explored. Results: The prevalence of the MetS was 21.7 % and 3.7 % in obese and overweight children, respectively. The balance of adipokines was disturbed in obesity, as the serum level of adiponectin decreased as body weight increased, while the serum level of leptin increased. The serum level of the inflammatory marker CRP increased significantly as body weight increased. Discriminant analysis showed that these factors could distinguish the children with MetS as compared to children with no MetS. Conclusions: In the under study Mediterranean childhood population, monitoring of the levels of adipokines and CRP could identify the overweight and obese children with MetS. Appropriate individualized dietary and lifestyle interventions can be applied in these children to prevent health complications associated with MetS.